Penyelesaian Tindak Pidana Penganiayaan terhadap Kepala Sekolah Di Kabupaten Tanjung Jabung Barat - Rizan Pratama; Sumaidi Sumaidi (Wajah Hukum, 2022)
The teaching profession and the lecturer profession are special fields of work carried out based on principles, one of which is having guaranteed legal protection in carrying out professional duties. In addition, obtaining protection in carrying out their duties is one of the rights obtained by teachers in carrying out their professional duties. The type of research used is empirical juridical, and the nature of the research is descriptive, using primary and secondary data. Primary data obtained by means of interviews. Secondary data is obtained by means of literature study or documentation study. Then, all data and information were processed using qualitative data analysis. Based on the results of the study, it is understood that in realizing restorative justice as an alternative in resolving the Crime of Persecution Against the Head of State Middle School 10, Tanjung Jabung Barat Regency in order to avoid the difficulties that exist in the formal criminal justice process. And functioning does not cause public unrest or there is no community rejection, does not impact social conflict, all parties involved do not object, and relinquish the right to sue before the law. The obstacle faced in general is the difficulty of giving direction to the victim to resolve the case. only at the police level, but there is intervention from the victim's family who often insists on going to court. After the police provided input and gave many explanations regarding the consequences that the victim would receive if they wanted to proceed to the Court such as internal divisions, and In overcoming the obstacles faced by the umbrella sector police, they could only provide input and advice if there were obstacles, and The Crime of Persecution Against the Head of State High School 10 Tanjung Jabung Barat Regency Tanjung Jabung Barat Resort Police can overcome existing obstacles and provide restorative justice